Advances in Stellar Interferometry 2006
DOI: 10.1117/12.670409
|View full text |Cite
|
Sign up to set email alerts
|

2006 interferometry imaging beauty contest

Abstract: We present a formal comparison of the performance of algorithms used for synthesis imaging with optical/infrared long-baseline interferometers. Five different algorithms are evaluated based on their performance with simulated test data. Each set of test data is formatted in the OI-FITS format. The data are calibrated power spectra and bispectra measured with an array intended to be typical of existing imaging interferometers. The strengths and limitations of each algorithm are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…Goodman 2005). The proceedings of recent summer schools on optical interferometry are also very instructive in considering these instruments further (in particular, Lawson 2000;Haniff 2007aHaniff , 2007b, as is Bracewell (2000)'s book on the Fourier transform itself. In practice, an optical interferometer takes light from two or more telescopes and recombines in such a way that the light from the apertures combines coherently, or interferes with itself (hence the name).…”
Section: Observational Quantities Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Goodman 2005). The proceedings of recent summer schools on optical interferometry are also very instructive in considering these instruments further (in particular, Lawson 2000;Haniff 2007aHaniff , 2007b, as is Bracewell (2000)'s book on the Fourier transform itself. In practice, an optical interferometer takes light from two or more telescopes and recombines in such a way that the light from the apertures combines coherently, or interferes with itself (hence the name).…”
Section: Observational Quantities Predictionsmentioning
confidence: 99%
“…3 of Zhao et al (2009), who use the Maximum Entropy Method of radio synthesis imaging (Narayan and Nityananda 1986) as developed by Ireland et al (2006) into the "Markov-Chain Imager for Optical Interferometry" (MACIM) code. Blind tests of the results from MACIM (Lawson et al 2006) have shown it to be a robust tool for image reconstruction with optical interferometric data. For the application to rapid rotators, Zhao et al (2009) incorporated an ellipse prior, justified by the reasonable expectation that the stellar photosphere has a sharp cutoff at the edge.…”
Section: Image Reconstructionmentioning
confidence: 99%
“…All these algorithms have been compared on simulated data during Interferometric Beauty Contests [16], [60], [61]. The results of the contest were very encouraging.…”
Section: B Image Reconstruction Algorithmsmentioning
confidence: 99%
“…For this purpose, we employed the Building Block Mapping (BBM) image reconstruction algorithm 18 . This algorithm has already been employed successfully in various earlier projects to reconstruct interferometric images from simulated 19,20 and long-baseline interferometric data [21][22][23] . The reconstruction was performed on a 256 × 256 grid using a pixel scale of 0.85 mas/pixel and convergence was reached after ∼ 12 000 iteration steps.…”
Section: Aperture Synthesis Imagingmentioning
confidence: 99%